George Peabody Wetmore papers - Wetmore, George Peabody, 1846-1921.
Correspondence related primarily to the U.S. Commission of Fine Arts and to the improvement and development of Washington, D.C., including plans for the National Mall, historic sites, and memorials to Abraham Lincoln, Ulysses S. Grant, and other historical figures. Correspondents include R.A. Alger, Gutzon Borglum, John Hay, Alexander Mackay-Smith, Elihu Root, Augustus Saint-Gaudens, and William H. Taft.
Governor and U.S. representative and senator from Rhode Island.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Alger, R. A. -- 1836-1907 -- Correspondence; Borglum, Gutzon, -- 1867-1941 -- Correspondence; Grant, Ulysses S. -- 1822-1885 -- Monuments; Hay, John, -- 1838-1905 -- Correspondence; Lincoln, Abraham, -- 1809-1865 -- Monuments; Mackay-Smith, Alexander, -- 1850-1911 -- Correspondence; Root, Elihu, -- 1845-1937 -- Correspondence; Saint-Gaudens, Augustus, -- 1848-1907 -- Correspondence; Taft, William H. -- 1857-1930 -- Correspondence; United States. -- Commission of Fine Arts; Art and state -- United States; Art, Municipal -- Washington (D.C.); City planning -- Washington (D.C.); Historic sites -- Washington (D.C.); Monuments -- Washington (D.C.); Parks -- Washington (D.C.); Public works -- Washington (D.C.); Mall, The (Washington, D.C.); Governors -- Rhode Island; Representatives, U.S. Congress -- Rhode Island; Senators, U.S. Congress -- Rhode Island